PENINGKATAN PEMAHAMAN PERAN BPJS KESEHATAN PADA MASYARAKAT DI MASA PANDEMI COVID-19 (LOKASI: KELURAHAN SIDOMULYO, MEDAN TUNTUNGAN) - Rosnidar Sembiring; Saidin Saidin; Zulfi Chairi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
The Covid-19 pandemic that hit Indonesia in 2020 has caused increased fatalities and property losses. There is still no discovery of a vaccine that can cure patients infected with Covid-19, so that these patients have to be hospitalized according to their medical needs and this is of course cost a lot. Then the question is whether the cost of medical care at the hospital due to Covid-19 will be borne by BPJS Kesehatan (Healthcare and Social security Agency)? Due to that aboved concern, this paper would like to discuss how the role of BPJS Kesehatan in covering the costs of caring for patients with confirmed Covid-19 in health facilities? and second, what are the challenges and obstacles if BPJS Kesehatan covers the costs of caring for Covid-19 patients in health facilities? This research uses a normative juridical research with a descriptive analytical approach. The results showed that in this pandemic era, BPJS Kesehatan only acts as a verifier for hospital costs that treat patients confirmed Covid-19. Optimizing the role of BPJS Kesehatan as guarantor of health costs will encounter several challenges and obstacles, including the revision of Presidential Decree No. 82/2018, the health budget shall be being a priority for the government, as well as improving the governance of BPJS Health.